Evaluating the training needs of female Qur’an teachers in Sultanate of Oman from their perspectives - Al-Sheibani, Hilal Abdullah Ahmed; bin Samah, Rosni (Journal of Educational and Psychological Sciences, 2019)
This research aimed to determine the training needs of female Qur’an teachers in Sultanate of Oman which are about the teaching skills and the impact of governorate’s variable (workplace) on the training needs of female Qur’an teachers in Sultanate of Oman. The descriptive approach is used in this research. The researcher developed the research’s instrument which contains 50 variables that represent the training skills in 10 dimensions. The constancy of the instrument was confirmed for the internal consistency based on the Cronbach’s alpha and the correlation coefficient showed that the measure has a high degree of structural honesty after the instrument was presented to a group of arbitrators. The sample consists of all female Qur’an teachers in Sultanate of Oman which was distributed randomly to 249 of them. Through using the SPSS, the results show that the level of training needs in its overall average gets 3.53 which estimated to be (high), and at the level of other fields, the averages ranged between 3.71 – 3.04 with ratings between (large-medium). The results showed statistically significant differences in the variable of the workplace (Governorate) regarding the training needs for the female Qur’an teachers in Sultanate of Oman, in favor of the governorates with the lowest averages as follows: Musandam Governorate, then Al Dhahira Governorate and at last Muscat Governorate. Based on the results, a number of recommendations and proposals were made to provide the most important training needs of teachers, design, and implementation of training programs according to needs, as well as proposals for further studies to complement the topic.